Derivative Spectrophotometric Determination of Lead(II) using Diacetylmonoxime-4-hydroxybenzoylhydrazone - NARENDER REDDY, G.; CHANDRASEKHAR, K.B.; DEVANNA, N.; JAYAVEERA, K.N. (Asian Journal of Chemistry, 2010)
Diacetylmonoxime-4-hydroxybenzoylhydrazone (DM-4- HBH) used as an analytical reagent for lead(II). This reagent gives bright yellow coloured water soluble complex in basic buffer solution. The maximum absorbance is observed at pH 10. The molar absorptivity and sandell's sensitivity of Pb(II) λmax at 440 nm was found to be 1.71 × 104 L mol-1 cm-1 and 0.01208 μg/cm2. Beer's law validity range 0.414-10.360 μg mL-1. Pb(II) forms 1:1 complex with DM-4-HBH and stability constant of the complex was 9.88 × 105. The first order derivative method has been developed. The derivative amplitude was measured by peak height method and shows maximum amplitude at 484 nm in basic buffer medium. The developed first order derivative spectrophotometric method was used for the determination of Pb(II) in synthetic alloy samples.